Oracle Identity Management: Governance, Risk, and Compliance Architecture, Third Edition - Pohlman, Marlin (CRC Press, 2009)
In today’s competitive marketplace with its focus on profit, maintaining integrity can often be a challenge. Further complicating this challenge is the fact that those assigned to the task of assuring accountability within an organization often have little, if any, visibility into the inner workings of that organization.